The paradoxical role of cytokines and chemokines at the tumor microenvironment: a comprehensive review - Toufik Abdul-Rahman; Shankhaneel Ghosh; Sarah M. Badar; Abubakar Nazir; Gafar Babatunde Bamigbade; Narjiss Aji; Poulami Roy; Hajar kachani; Neil Garg; Lukman Lawal; Zarah Sophia Blake Bliss; Andrew Awuah Wireko; et al. (European Journal of Medical Research, 2024)
Abstract Tumor progression and eradication have long piqued the scientific community's interest. Recent discoveries about the role of chemokines and cytokines in these processes have fueled renewed interest in related research. These roles are frequently viewed as contentious due to their ability to both suppress and promote cancer progression. As a result, this review critically appraised existing literature to discuss the unique roles of cytokines and chemokines in the tumor microenvironment, as well as the existing challenges and future opportunities for exploiting these roles to develop novel and targeted treatments. While these modulatory molecules play an important role in tumor suppression via enhanced cancer-cell identification by cytotoxic effector cells and directly recruiting immunological effector cells and stromal cells in the TME, we observed that they also promote tumor proliferation. Many cytokines, including GM-CSF, IL-7, IL-12, IL-15, IL-18, and IL-21, have entered clinical trials for people with advanced cancer, while the FDA has approved interferon-alpha and IL-2. Nonetheless, low efficacy and dose-limiting toxicity limit these agents' full potential. Conversely, Chemokines have tremendous potential for increasing cancer immune-cell penetration of the tumor microenvironment and promoting beneficial immunological interactions. When chemokines are combined with cytokines, they activate lymphocytes, producing IL-2, CD80, and IL-12, all of which have a strong anticancer effect. This phenomenon opens the door to the development of effective anticancer combination therapies, such as therapies that can reverse cancer escape, and chemotaxis of immunosuppressive cells like Tregs, MDSCs, and TAMs.